Platelet role in the prediction of MIS-C severity - Snipaitiene, Ausra; Sirataviciene, Aurelija; Varoneckaite, Leila; Sileikiene, Rima; Jankauskaite, Lina (Frontiers in Pediatrics, 2023)
Introduction: Multisystem inflammatory syndrome in children (MIS-C) has been described as one of the cytokine storm syndromes associated with COVID-19. Despite the several proposed diagnostic criteria, MIS-C remains a diagnostic and clinical challenge. Recent studies have demonstrated that platelets (PLT) play a crucial role in COVID-19 infection and its prognosis. This study aimed to investigate the clinical importance of platelet count and platelet indices in predicting the severity of MIS-C in children. Patients and methods: We conducted a retrospective single-center study at our university hospital. 43 patients during the two-year period (from October 2020 to October 2022) diagnosed with MIS-C were included into the study. The MIS-C severity was evaluated according to the composite severity score. Results: Half of the patients were treated in the pediatric intensive care unit. None of the single clinical signs were associated with severe condition, except for shock (p=0.041). All the routine biomarkers, such as CBC, CRP etc., used for MIS-C diagnosis were significant in predicting the severity of MIS-C. Single PLT parameter, such as mean platelet volume, platelecrite or platelet distribution width did not differ between the severity groups. However, we found that a combination of PLT count and previously mentioned PLT indices had the potential to predict MIS-C severity. Conclusions: Our study emphasizes the importance of PLT in MIS-C pathogenesis and severity. It revealed that together with routine biomarkers (e.g., CBC, CRP, etc.) it could highly improve MIS-C severity prediction.